DORSAL DISTRIBUTION OF HAIR ON THE PHALANGES OF HAND IN SUB- URBAN AREA OF HYDERABAD - RAMESWARAPU SUMAN BABU; DAVID ANAND KUMAR .P; SUJATHA .P (International Journal of Pharma and Bio Sciences, 2013)
In humans, hairs are common, in man it is a special and cherished feature especially in females. Hair is a filamentous keratinized structure present over almost the entire body surface (Jungueira and Carneiro, 2005). One hundred and twenty four subjects comprising of 61 females and 63 males, aged 21-41 years were randomly selected from medchal town. Phalangeal hair distribution was inspected physically on the dorsum of the hands of the subjects. Gender and phalangeal hair patterns were observed and categorized. Fisher`s exact test was used to assess the relationship between gender and patterns. Result shows hair distribution patterns 1-2-3-4-5 (10%), 2-3-4-5 (54%), 2-3-4 (3%), 3-4-5 (16%), 3-4 (9%). One percent were without hair in there proximal phalanges. Result also shows that 0% occurrence of hair in the distal phalanges. The pattern 3-4 shows a significance female preponderance. This study also established that interethnic and racial variations exist in phalangeal hair distribution. Hence, confirming that biological anthropologic trait varies amongst various human populations.